Flexible free-standing composite films having 3D continuous structures of hollow graphene ellipsoids - Lee, Eun Goo; Shin, Keun-Young; Lee, Jonghwi; Lee, Sang-Soo (POLYMER SOC KOREA, 2015)
Graphene composites have great potential in electrical and electronic applications due to their outstanding physicochemical, electrical, and mechanical properties. Unfortunately, current graphene preparation technologies allow the exploitation of only an exceptionally low percentage of graphene's capability. Herein, free-standing graphene films based on three-dimensional (3D) continuous structures of hollow graphene ellipsoids were successfully fabricated, whose composite structure has never been investigated. Positively charged polystyrene (PS) spheres were first wrapped with negatively charged graphene upon simple mixing, and became ellipsoids by stretching. Due to their improved continuity, composites based on the ellipsoids and spherical microparticles have lower sheet resistances than those based on spherical nanoparticles. Upon folding and application of pressure, composites based on the hollow graphene ellipsoids exhibited superior electrical conductivity and structural stability owing to their high mechanical strength and effective electron transport pathway. The ability to control the face-contact structures of graphene in a polymer matrix by means of particle morphology represents an effective strategy for future composite engineering.
Keywords: SHEETS; ENERGY